Design of leaky wave antenna with composite right-/left-handed transmission line structure for circular polarization radiation - Ishii, Masahiko. (2014)
This paper presents a design procedure for the generation of circular polarization (CP) from the composite right/left handed (CRLH) transmission line-(TL) with a coupled inter-digit structure and an inductive stub. The Ex and Ey components are generated from the parallel stubs and the fingers, respectively. The 90°-phase difference can be obtained by optimizing the dimension of the unit cell. In addition, the suitable amplitude ratio of |Ex| and |Ey| for CP generation is obtained by selecting a suitable position of the CRLH-TL between both edges of the ground. As a result, a CP with a measured bandwidth of 30.5% for an axial ratio (AR) of < 3 dB in the boresight direction is obtained. Using the behavior in both the left-handed (LH) and right-handed (RH) frequency regions, a scanning angle of the main beam of approximately 30° can be obtained by varying the frequency between 2.58 GHz and 2.99 GHz. Furthremore, the principle of CP generation is discussed.